Selection of electrochemical and electrical energy storage systems for off-grid renewable energy mini-grids: A review - Isaac Gwayi; Sarah Paul Ayeng’o; Cuthbert Z.M. Kimambo (Cleaner Engineering and Technology)
Application of electrochemical energy storage systems (ESSs) in off-grid renewable energy (RE) mini-grids (REMGs) is crucial to ensure continuous power supply. These storage systems face accelerated degradation due to fluctuations in demand and supply power of the system. Although various research has been conducted in the field of ESSs, study on selecting appropriate ESSs for off-grid REMGs, considering power fluctuations impact, is still a gap which needs further research. This review study therefore, focused on studying and selecting appropriate electrochemical and electrical storage systems for off-grid REMGs through investigating their technical, economic and environmental factors. On economic factors investigation; capital recovery factor (CRF) and annualised cost (AC) of considered ESSs were used in this study. Comparison and analysis of technical and economic factors of the storage systems were done using graphical method. Results show that hybrid combination of lithium-ion (Li-ion) battery or lead acid (Pb-Acid) battery with supercapacitor (SC) are appropriate ESSs for off-grid REMGs. Furthermore, trade-offs between ESSs options are analysed and the study recommends hybridisation of Li-ion, Pb-Acid and SC to further improve performance of the hybrid storage. Finally, challenges in deploying the proposed hybrid energy storage system (HESS) configurations are discussed and areas needing further research for improvement are proposed.